Evolution of Sex Determination in Amniotes: Did Stress and Sequential Hermaphroditism Produce Environmental Determination? - Straková, Barbora; Rovatsos, Michail; Kubička, Lukáš; Kratochvíl, Lukáš (BioEssays, 2020)
Frequent independent origins of environmental sex determination (ESD) are assumed within amniotes. However, the phylogenetic distribution of sex-determining modes suggests that ESD is likely very ancient and may be homologous across ESD groups. Sex chromosomes are demonstrated to be old and stable in endothermic (mammals and birds) and many ectothermic (non-avian reptiles) lineages, but they are mostly non-homologous between individual amniote lineages. The phylogenetic pattern may be explained by ancestral ESD with multiple transitions to later evolutionary stable genotypic sex determination. It is pointed out here that amniote ESD shares several key aspects with sequential hermaphroditism of fishes such as a lack of sex differences in genomes, biased population sex ratios, and potentially also molecular mechanism related to general stress responses. Here, it is speculated that ESD evolves via a heterochronic shift of the sensitive period of sex change from the adult to the embryonic stage in a hermaphroditic amniote ancestor. Also see the video abstract here https://youtu.be/q2mjtlCefu4.
Keywords: biologická evoluce; Male; Sex Chromosomes; sex changes; poruchy sexuálního vývoje; mužské pohlaví; pohlavní chromozomy; Disorders of Sex Development; Sex Determination Processes; stress; Biological Evolution; amniotes; environmental sex determination; procesy určující pohlaví; ženské pohlaví; zvířata; fylogeneze; sex chromosomes; Female; sequential hermaphrodites; Phylogeny; heterochronies; Animals